Ethnic Identity, Implicit Associations, and Academic Motivation of Hispanic Adolescents - Tim Urdan; Daniel Teramoto (MDPI AG, 2021)
One of the major tasks of adolescence is to integrate the different aspects of identity into a coherent sense of self. Prior research has found that under certain circumstances, students who identify as members of groups about which there are negative stereotypes can experience a disassociation between their academic identity (i.e., academic self-concept) and the aspect of their identity that is negatively stereotyped (i.e., their ethnic or gender identity). In this study, we examined the association between ethnic identity, academic self-concept, valuing of school, and feelings of belonging among a sample of Hispanic high school students attending a majority-Hispanic high school. In addition, we used an Implicit Associations Test (IAT) to assess their implicit associations between success and ethnic group (Hispanic or white). Results indicated that centrality of ethnic identity was positively correlated with academic self-concept and the regard dimension of ethnic identity was associated with feelings of belonging. The IAT indicated that Hispanic students had implicitly associated success more with being white than with being Hispanic.